2008
DOI: 10.1159/000177025
|View full text |Cite
|
Sign up to set email alerts
|

Role of Repeated Endoscopic Ultrasound-Guided Fine Needle Aspiration in Small Solid Pancreatic Masses with Previous Indeterminate and Negative Cytological Findings

Abstract: Introduction: Despite advances in imaging techniques, the differentiation between pancreatic cancer and benign lesions remains difficult. Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is an effective method for providing tissue diagnosis, but problems occur when lesions are small or the cytological diagnosis is indeterminate. Aim: To prospectively evaluate the utility of EUS-FNA in patients with small solid pancreatic lesions and those with initial indeterminate or negative cytological diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…To increase this value, a higher number of passes [11], a proper selection of adequate material [6] or guidance under contrast enhancement can be performed [21]. Other reports showed that repeating the EUS-FNA in the case of an initially negative cytology increased the yield of diagnosis [25][26][27], as in our group of patients, where the diagnostic rate increased to 96%, despite some delay for obtaining the final diagnosis.…”
Section: Discussionmentioning
confidence: 52%
“…To increase this value, a higher number of passes [11], a proper selection of adequate material [6] or guidance under contrast enhancement can be performed [21]. Other reports showed that repeating the EUS-FNA in the case of an initially negative cytology increased the yield of diagnosis [25][26][27], as in our group of patients, where the diagnostic rate increased to 96%, despite some delay for obtaining the final diagnosis.…”
Section: Discussionmentioning
confidence: 52%
“…This will improve the diagnostic yield. 34 Of our six false-negative cases, four were surgically treated (three adenocarcinomas and one neuroendocrine tumour) and the patient with a malignant IPMN died of his disease 5 months after FNA. The last case is a matter of debate.…”
Section: Discussionmentioning
confidence: 85%
“…Endoscopic ultrasound-guided FNB with a ProCore needle may also represent a cost-saving choice because if the diagnostic ability of EUS-FNA with a standard needle was lower for smaller lesions, repeated procedures may be needed in order to increase diagnostic accuracy if malignancy is suspected, with an increment in cost [17].…”
Section: Discussionmentioning
confidence: 99%